Pendampingan Masyarakat Dan Penguatan Moderasi Islam Kepada Masyarakat Sampang Korban Konflik Syi’ah Di Rumah Susun Puspa Agro Sidoarjo - Miftahul Ulum (LPPM Universitas Yudharta Pasuruan, 2019)
After providing assistance and various discussions, moderation of Islam needs to be carried out continuously especially for the marginalized, especially the people of Syi'ah Sampang and the people who perpetrated the arson and riots in the Sampang Sunni-Shia conflict that occurred seven years ago. As a result of discussions with various approaches that the Syi'ah Sampang community who were displaced in Puspa Agro Flats wanted to get legal certainty and justice and were able to return to their home villages. After the author carried out community assistance to the Sampang community victims of the Sampang Syiah conflict in the Puspa Agro Sidoarjo Flats, the authors concluded that it was necessary to conduct continuous and continuous assistance, given the complexity of changing the mindset and mindset of many people, especially regarding trust or belief in religion.